2018
DOI: 10.1108/jmd-12-2016-0315
|View full text |Cite
|
Sign up to set email alerts
|

The mediation effect of customer satisfaction in the relationship between service quality, service orientation, and marketing mix strategy to customer loyalty

Abstract: Purpose -The purpose of this paper is to investigate the mediation effect of customer satisfaction in the relationship between service quality, service orientation, and marketing mix strategy to customer loyalty, in a study in Telkomsel-Indonesia. The product used in this research will take the telecommunication service product categories with a number of products available in the market. In this research, the telecommunication service products of Telkomsel with various features as the research objects were st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
92
1
33

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(135 citation statements)
references
References 32 publications
(13 reference statements)
9
92
1
33
Order By: Relevance
“…Equivalent product dimension and location have no significant effect to satisfaction. Furthermore, the determinant between product, promotion, set tariff, location, process, employees and environment of hotel physics to satisfaction is equal to 0.56(Achmad Rinaldo Fernandes, A., & Solimun, 2018). This means that the hotel user satisfaction is 0.56 is from the above dimensions, while the remaining 0.44 is from other factors outside this study.…”
Section: Discussionmentioning
confidence: 87%
“…Equivalent product dimension and location have no significant effect to satisfaction. Furthermore, the determinant between product, promotion, set tariff, location, process, employees and environment of hotel physics to satisfaction is equal to 0.56(Achmad Rinaldo Fernandes, A., & Solimun, 2018). This means that the hotel user satisfaction is 0.56 is from the above dimensions, while the remaining 0.44 is from other factors outside this study.…”
Section: Discussionmentioning
confidence: 87%
“…However, the effect of system quality on bike sharing users' continues usage intention was not significant. Prior research showed that service quality could affect users' satisfaction and loyalty in the marketing area [64]. This paper found that service quality could affect users' satisfaction, which subsequently influenced users' continued usage intentions.…”
Section: Key Findingsmentioning
confidence: 82%
“…Secondly, WOM plays a mediating role between cost or price of a product or service and its ultimate perception regarding quality in the minds of the customers (Solimun & Fernandes, 2018). Similarly, according to Jiang et al (2016), word-of-mouth marketing regarding pricing of product also helps increasing customer perception.…”
Section: H M1: Word Of Mouth Mediates the Interface Between Product Amentioning
confidence: 99%